DEVELOPMENT OF FINANCIAL BENEFIT CALCULATION MODEL USING WAREHOUSE RECEIPT SCHEME FOR SHALLOTS - WIDYANTINI (NIM : 23411039); Dosen Pembimbing : Dr. Tota Simatupang, RAHAYU
Shallots is one of the commodities needed by households and industry, although its existence is not one of the staple food but inflation caused by price fluctuations of shallots is very influential. Price fluctuations that occur at the consumer level does not necessarily provide high profits for farmers. Several studies have been done to stabilize prices, including through the buffer stock. Model development of buffer stock with product deterioration during storage has also been done for sugar commodity. While the shallots is very different characteristics with sugar, where the shallots harvest occurs three times in a year. Thus, it is considered that the development of a model of the warehouse receipt benefits calculation for product deterioration such as shallots needs to be done. The focus of this study is to calculate the amount of benefits obtained by any entity involved in warehouse receipt scheme for shallots. Mathematical modeling is used for the calculation of benefits producers, warehouse managers, traders and consumers. The data used is the supply and demand in 2010. Performance criteria in this study is the total benefit system. Model development results show that the model can provide benefits to each entity involved in the warehouse receipt system which excluded large speculative traders. Calculation of decision variables in the model design is done with three scenarios, with consideration of price increases, consideration of information supply and demand balances, consideration of price expectation form. Scenarios with the consideration of the balance of supply and demand provide a greater number of benefits for farmers compared to scenarios which price fluctuations as the consideration.